ANALISIS PENGUBAHAN TINGKAH LAKU PERSPEKTIF PSIKOLOGI KONSELING (Mekanisme Rehabilitasi Bagi Pengguna Narkotika di BNNP Maluku) - Jumail Jumail; Agus Wibowo (Psikodidaktika, 2020)
This study aims to determine the behavior changes experienced by narcotics users through rehabilitation mechanisms in the perspective of counseling psychology. The method used in this research is qualitative with a psychological approach. informants in the study were 10 people. The instruments, used awere observation guidelines, interview guidelines and documentation. Data analysis techniques in research used Miles and Huberman model. the results showed that psychologists and counselors had made rehabilitation mechanisms for narcotics users well. This can be seen from narcotics users who have new understanding, stable emotions, and can take advantage of their abilities into job opportunities.